Methylphenidate treatment of a Chinese boy with Becker muscular dystrophy combined with attention deficit hyperactivity disorder: a case report - Shen, Fang; Zhou, Hui (Frontiers in Neuroscience, 2024)
BackgroundBecker muscular dystrophy (BMD) is an X-linked recessive inherited disorder characterized by slowly progressing muscle weakness of the legs and pelvis, caused by mutations in the DMD gene, which encodes dystrophin protein. Different from Duchenne Muscular Dystrophy (DMD), in which dystrophin is completely absent in muscle tissue, while in BMD, the dystrophin gene can express some protein, but not enough. It has also been shown that a proportion of patients with DMD suffer from attention deficit hyperactivity disorder (ADHD), and the use of the stimulant methylphenidate has been suggested for the treatment of patients with DMD in combination with ADHD. However, there are no case reports on the treatment of co-occurring ADHD in BMD.Case presentationThe patient was a 9-year-old boy who presented with elevated serum creatine kinase levels and inattention. The magnetic resonance imaging of the thigh muscles of both lower limbs suggested partial fatty infiltration of the gluteus maximus muscle bilaterally, and a novel heterozygous mutation (c.31 + 6 T > C) was identified in the DMD gene by Next Generation Sequencing (NGS) and the sequencing results were verified by using the Sanger method. The child was also diagnosed with co-morbid ADHD after a thorough evaluation and considering this new diagnosis, we started treatment with methylphenidate at a dose of 18 mg/day, and after 6 months of treatment, he showed a significant improvement in his attention span.ConclusionWe identified a novel heterozygous mutation in the DMD gene, which will expand the spectrum of pathogenic variants in BMD. Simultaneously, methylphenidate treatment significantly improved attention in children with BMD co-morbid with ADHD, and this study provides value for future therapeutic protocols for BMD combined with ADHD. However, to the best of our knowledge, this is the only reported case report on the treatment of BMD co-morbid ADHD. So further studies are needed to determine the interrelationship between these disorders and their treatment.